2017
DOI: 10.3389/fnhum.2017.00373
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Inhibitory Control between Impulsive and Premeditated Aggression in Juvenile Inmates

Abstract: Inhibitory control dysfunction was considered a universal characteristic of violent offenders. The aim of this study was to examine differences in inhibitory control between two subtypes of violent youth; those displaying predominantly impulsive and those presenting predominantly premeditated aggression (PM). Forty-four juvenile offenders, defined on the basis of the Procedures for the Classification of Aggressive/Violent Acts (Stanford and Barratt, 2001) participated (N = 23: impulsive; N = 21 premeditated). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…Previous studies using non-emotional Go/No-go tasks have found that the N2 Go/No-go difference wave is negatively correlated with impulsivity in aggression in juvenile violent offenders, and impulsive violent offenders demonstrate a smaller amplitude in the N2 Go/No-go difference wave relative to matched controls (Chen et al, 2005;Zhang et al, 2017). The present study recruited participants from the normal population and used the emotional Go/No-go paradigm.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies using non-emotional Go/No-go tasks have found that the N2 Go/No-go difference wave is negatively correlated with impulsivity in aggression in juvenile violent offenders, and impulsive violent offenders demonstrate a smaller amplitude in the N2 Go/No-go difference wave relative to matched controls (Chen et al, 2005;Zhang et al, 2017). The present study recruited participants from the normal population and used the emotional Go/No-go paradigm.…”
Section: Discussionmentioning
confidence: 88%
“…Reactive aggression is characterized by a spontaneous emotion-driven response to perceived provocation, while proactive aggression, on the other hand, is characterized by deliberate, non-emotional behavior to obtain a specified goal (Crick and Dodge, 1996). Response inhibition was found to be related to reactive aggression but not to proactive aggression (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Low IC may be one of the reasons why youth from low socioeconomic status (SES) and racial and ethnic minority groups engage in more risky behaviors, compared to high SES and majority youth [1,[13][14][15][16]. Thus, studies are needed that investigate the additive effects of race/ethnicity and SES on youth IC as a mechanism of disparities and inequalities in high-risk behaviors [1,10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Aggression is a heterogeneous behavioural phenomenon both in form (physical, verbal, relational), function (defensive, instrumental) and implementation (with or without premeditation) . Throughout childhood and adolescence, overt physical aggression peaks and individual differences stabilize, and only a subgroup of children who are highly aggressive in early childhood remain so in later life, as desistance in physical aggression over childhood is well‐established .…”
Section: Serotonergic Biosynthesis and Metabolismmentioning
confidence: 99%